2022
DOI: 10.1038/s41596-021-00664-5
|View full text |Cite
|
Sign up to set email alerts
|

A checklist for assessing the methodological quality of concurrent tES-fMRI studies (ContES checklist): a consensus study and statement

Abstract: Low-intensity transcranial electrical stimulation (tES), including alternating or direct current stimulation, applies weak electrical stimulation to modulate the activity of brain circuits. Integration of tES with concurrent functional MRI (fMRI) allows for the mapping of neural activity during neuromodulation, supporting causal studies of both brain function and tES effects. Methodological aspects of tES-fMRI studies underpin the results, and reporting them in appropriate detail is required for reproducibilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 109 publications
0
29
0
Order By: Relevance
“…We used a Delphi technique, in which comments and feedback are iteratively discussed (Hsu and Sandford, 2019), for addressing challenges and proposing recommendations for digitizing tES trials. Following recent papers (Ekhtiari et al, 2022a(Ekhtiari et al, , 2022b, we initially convened a steering committee (SC) group, formed based on the collaborative network of the leading authors, to develop structured questionnaires with items using Five-point Likert scales or open questions (Supplementary Material -Appendix 2). The SC also provided qualitative feedback on several topics that were analyzed by the leading authors and qualitatively described here.…”
Section: Specialist Panelmentioning
confidence: 99%
“…We used a Delphi technique, in which comments and feedback are iteratively discussed (Hsu and Sandford, 2019), for addressing challenges and proposing recommendations for digitizing tES trials. Following recent papers (Ekhtiari et al, 2022a(Ekhtiari et al, , 2022b, we initially convened a steering committee (SC) group, formed based on the collaborative network of the leading authors, to develop structured questionnaires with items using Five-point Likert scales or open questions (Supplementary Material -Appendix 2). The SC also provided qualitative feedback on several topics that were analyzed by the leading authors and qualitatively described here.…”
Section: Specialist Panelmentioning
confidence: 99%
“…Further validation, particularly under the systematic procedure of simultaneous tES-fMRI (Ekhtiari et al, 2022 ) of the proposed methodology, is suggested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated an open-source fMRI-tDCS dataset [53] that used a TR=3.36sec and captured 0.052-0.145 Hz associated with smooth muscle cell activity, including 'initial dip' that is postulated via norepinephrine receptors on the pial arterial SMCs [14,15] that can modulate hemodynamics (from arterioles as they transition into capillaries). Ekhtiari and colleagues [54] recently published a checklist for assessing the methodological quality of concurrent transcranial electrical stimulation (tES)-functional magnetic resonance imaging (fMRI) studies; however, the protocol did not elaborate on the methods for separating tES effect on the neuronal activation from the effect on the neurovascular coupling [9], i.e., the hemodynamic response function (HRF). Here, mapping of the tES stimulus-related Blood Oxygen Level Dependent (BOLD) signals measured using fMRI is usually achieved by fitting a general linear model (GLM) to the time course with a pre-specified canonical HRF model, e.g., double-gamma function [55].…”
Section: Modal Analysis Of the Physiologically Detailed Neurovascular...mentioning
confidence: 99%